Disparity in circulating adiponectin multimers between term and preterm infants. - Tania Siahanidou; Margeli, Alexandra; Garatzioti, Maria; Davradou, Maria; Apostolakou, Filia; Papassotiriou, Ioannis; Mandyla, Helen (J Perinat Med, 2009)
AIMS: To study circulating levels and distribution of adiponectin multimers [low molecular weight (LMW)-, medium molecular weight (MMW)- and high molecular weight (HMW)-adiponectin] in preterm and full-term infants. METHODS: Total serum adiponectin and its multimers were measured in 40 healthy infants at the age of one month and associations with anthropometric parameters [body weight and length, body mass index (BMI)], weight gain and metabolic indices (glucose, insulin) were examined. Twenty of the infants were born preterm (gestational age 33.2+/-1.6 weeks). RESULTS: LMW-adiponectin level and its fractional ratio to total adiponectin were significantly higher in full-term than in preterm infants (P<0.001 and P<0.01, respectively), whereas, MMW-adiponectin level and its ratio were significantly lower (P=0.03 and P=0.01, respectively). HMW-adiponectin did not differ significantly between full-term and preterm infants and accounted for almost 60% of total adiponectin levels in both groups. HMW-adiponectin, but not MMW adiponectin or LMW adiponectin, correlated significantly with anthropometric measurements, similarly to total adiponectin; in addition, HMW adiponectin correlated significantly with weight gain. CONCLUSIONS: HMW adiponectin is the most prevalent form in infants. Circulating levels and distribution of MMW- and LMW-adiponectin differ between full-term and preterm infants, but the role of these adiponectin multimers needs to be studied further.
Keywords: Adiponectin; Birth Weight; Body Mass Index; Case-Control Studies; Female; Gestational Age; Humans; Infant; Male; Molecular Weight; Newborn; Pregnancy; Premature; Protein Structure; Quaternary; Weight Gain